2017
DOI: 10.1109/tim.2017.2648598
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Phase Comparator for Characterization of Devices for PMUs Calibrator

Abstract: This paper reports recent progress in developing a new asynchronous digital phase comparator for the precision measurement of phase difference of voltage ratio devices and calibration of functional elements of PMUs calibrator. The phase error of the proposed digital comparator is below 300 nrad at 50 Hz and 100 µrad at 100 kHz with applied voltages ranging between 500 mV and 3 V, whereas the phase error of cables and connectors was estimated to be 4 µrad at 1 MHz. Besides resistive dividers, the phase comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The quantity u g f 0 ð Þ can be measured with a phase comparator (COMP) (Crotti et al, 2017;Trinchera et al, 2017) and the quantity t c can be measured with a frequency counter. The phase angle, u TOT , of the DUT samples, at frequency f 0 , can be evaluated by performing the Discrete Fourier Transform (DFT) and expressed as ]F s DUT kT s ð Þ ½ j f0 ; thus, the DUT phase error, at frequency f 0 , can be calculated as…”
Section: Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity u g f 0 ð Þ can be measured with a phase comparator (COMP) (Crotti et al, 2017;Trinchera et al, 2017) and the quantity t c can be measured with a frequency counter. The phase angle, u TOT , of the DUT samples, at frequency f 0 , can be evaluated by performing the Discrete Fourier Transform (DFT) and expressed as ]F s DUT kT s ð Þ ½ j f0 ; thus, the DUT phase error, at frequency f 0 , can be calculated as…”
Section: Measurement Methodsmentioning
confidence: 99%
“…), this effect reduces its impact because phase subtraction leads to the compensation this systematic effect. Nevertheless, the issues related with measurement of the relative phase delay between two channels of the same digitizer, or two channels of two different digitizers with synchronized sampling clocks, are faced in a number of scientific papers (Bosco et al, 2011;Crotti et al, 2017;Trinchera et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the research on the definition of accurate phasor estimation algorithms [48][49][50][51], the implementation of reference class hardware test systems is of key importance to the successful deployment of PMUs in Smart Grids. Researchers and national metrological institutes have developed in-house test facilities [52][53][54][55][56][57][58][59] and employed off-the-shelf solutions [60][61][62]. The architecture of PMU calibrators is quite consolidated.…”
Section: The Calibrator Hardware Architecturementioning
confidence: 99%
“…Conversely, it is observed that the level of calibrations is increased. With the aforementioned difficulties that crafts traceable magnitude and phase calibration for ac signals, active and passive components and extend the automatic finding and correcting the bias error have been analysed [10][11][12]. Despite the facts, the models detailed provide an iterative based elucidation.…”
Section: State-of-the Art Workmentioning
confidence: 99%